Literature Review: Implementation of Carbon Tax in Indonesia - Putra, Samuel Niko; Astuti, Melinda; Munandar, Agus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Climate change is an international issue that requires fast and decisive action from many countries, including Indonesia, to set a carbon price to reduce greenhouse gas emissions, which are the main drivers of climate change. In Indonesia, one of the initiatives to reduce carbon emissions is the implementation of a carbon tax. This study uses a qualitative methodology and a literature review to provide comprehensive knowledge of how Indonesia implements carbon pricing. The results show that the Indonesian government took a proactive approach to addressing problems caused by climate change when implementing the Carbon Tax. The policies set by the government provide a strong basis for implementing the Carbon Tax.